(untitled) (Communications in Mathematical Research, 2021)
Let γ^∗ (D) denote the twin domination number of digraph D and let D_1 ⊗ D_2 denote the strong product of D_1 and D_2. In this paper, we obtain that the twin domination number of strong product of two directed cycles of length at least 2. Furthermore, we give a lower bound of the twin domination number of strong product of two digraphs, and prove that the twin domination number of strong product of the complete digraph and any digraph D equals the twin domination number of D.